GRA.LE.D. (GRApevine LEaf Digitalization) Software for the Detection and Graphic Reconstruction of Ampelometric Differences Between Vitis Leaves - Bodor, P.; Baranyai, L.; Bálo, B.; Tóth, E.; Strever, A.; Hunter, J.J.; Bisztray, Gy.D. (South African Journal of Enology and Viticulture, 2016)
Raster graphic ampelometric software was not exclusively developed for the estimation of leaf area, but also for the characterization of grapevine (Viti vinifera L.) leaves. The software was written in C++ programming language, using the C++ Builder 2007 for Windows 95-XP and Linux operation systems. It handles desktop-scanned images. On the image analysed with the GRA.LE.D., the user has to determine 11 points. These points are then connected and the distances between them calculated. The GRA.LE.D. software supports standard ampelometric measurements such as leaf area, angles between the veins and lengths of the veins. These measurements are recorded by the software and exported into plain ASCII text files for single or multiple samples. Twenty-two biometric data points of each leaf are identified by the GRA.LE.D. It presents the opportunity to statistically analyse experimental data, allows comparison of cultivars and enables graphic reconstruction of leaves using the Microsoft Excel Chart Wizard. The GRA. LE.D. was thoroughly calibrated and compared to other widely used instruments and methods such as photo-gravimetry, LiCor Li3100, WinDIAS2.0 and ImageTool. By comparison, the GRA.LE.D. presented the most accurate measurements of leaf area, but the LiCor Li3100 and the WinDIAS2.0 were faster, while the photo-gravimetric method proved to be the most time-consuming. The WinDIAS2.0 instrument was the least reliable. The GRA.LE.D. is uncomplicated, user-friendly, accurate, consistent, reliable and has wide practical application.